Pharmacognostic evaluation of Lasimorpha senegalensis schott leaves (Araceae) - Ginikachukwu MaryRose Okoh; Obinna Sabastin Onugwu; Obodike Christopher Ezugwu (African Journal of Pharmaceutical Research and Development (AJOPRED))
The leaves of Lasimorpha senegalensis Schott (Araceae) have long been utilized in conventional medicine to treat conditions like diabetes, inflammation, malaria, oxidative stress, and fever. However, its properties have not been standardized to prevent adulteration. The purpose of this research is to determine Lasimorpha senegalensis Schott's numerous pharmacognostic, physicochemical, and phytochemical parameters. Fresh leaf samples and dried leaf powder were examined macroscopically and microscopically. The physicochemical and phytochemical parameters were determined using the standard methods. Fresh leaves have a unique scent and are dark green in colour, leathery texture, and acute apex. In addition to lacking trichomes, they have calcium oxalate crystals, starch grains, xylem, phloem, epidermal cells, and collenchyma cells. There was no mucilage, but lignin, starch, cellulose, oil globules, and calcium oxalate crystals were found by chemomicroscopic examination. The physicochemical assessment showed 9.2 % moisture content, 8.4 % total ash value, 0.9 % acid insoluble ash value, 2.6 % water soluble ash value, 16.5 % water soluble extractive value, and 41.5 % alcohol soluble extractive value. The qualitative phytochemical test identified tannins, glycosides, alkaloids, terpenoids, phenols, and flavonoids, as well as trace amounts of steroids, saponins, and hydrogen cyanides. This study provided valuable insight into the pharmacognostic standardization of L. senegalensis leaves and can be used to create a monograph and prevent adulteration of this important leaf plant.